Lovers and haters : a love and rockets book - Hernandez, Gilbert (Fantagraphics Books, 2025)
"In the next chapter of the Palomar saga, actress Fritz contends with a sex cult, mad scientists, and her inner demons. The first story collection in Gilbert Hernandez's Palomar saga to take place after the events of 2010's High Soft Lisp is torn from the pages of Love and Rockets: New Stories, Love and Rockets Vol. IV, and Psychodrama Illustrated-and expanded with 14 new pages! In Lovers and Haters, 50-year-old cult movie actress Fritz, in addition to her alcoholism and the ups and downs of her career, must also contend with a controlling lover, Danny; a jealous rival, Mila; a score of younger Fritz imitators, a sex cult; and mad scientists. Also in her orbit is her niece, Killer (sometimes literally, as seen in a Doctor Who-inspired TV show), a teen actress trying to launch a singing career while solving math problems. The specter of Fritz's mother, Maria - also a cult movie actress - haunts them all with her beauty from beyond the grave. With a sprawling cast, Lovers and Haters is about mothers and daughters, aunts and nieces, complex and often toxic relationships, artists and exploiters, personas and obsessions. It reads like an X-rated The Substance mixed with Mommy Dearest and Performance, with an added dash of giallo"--Publisher's website.